Arthritis complicating inflammatory bowel disease— the future is now - Song, K; Satsangi, J; Coates, LC (Elsevier, 2024)
Fundamental advances are occurring across immune-mediated inflammatory diseases. Recent therapeutic developments include strategies to prevent rheumatoid arthritis in high-risk individuals, using baseline cellular immunophenotypes to predict response to biologics in psoriatic arthritis, and using biologics in a top-down approach for Crohn's disease. However, meaningful progress has not occurred in the management of patients with spondyloarthropathy complicating inflammatory bowel disease (IBD). Currently, the pathophysiology of IBD-related spondyloarthropathy is poorly understood; moreover, there are no accepted or disease-specific screening tools, diagnostic criteria, or licenced treatments. Current approaches to clinical care from rheumatologists and gastroenterologists largely involve the extrapolation of spondyloarthropathy and IBD clinical guidelines, respectively, despite increasing recognition of IBD-related spondyloarthropathy being its own entity, with a unique phenotype. There is an obvious contrast between spondyloarthropathy complicating IBD and the management of arthropathy complicating psoriasis, a disease area where defined diagnostic criteria and dedicated clinical trials allow clear management guidelines. We argue that the time has come for a parallel approach and dedicated focus on IBD-related spondyloarthropathy.